Evaluation of the effectiveness of crocin isolated from saffron in treatment of burning mouth syndrome: A randomized controlled trial - Atessa Pakfetrat; Mahdi Talebi; Zohreh Dalirsani; Sayed Ahmad Mohajery; Roya Zamani; Ala Ghazi (Mashhad University of Medical Sciences, 2019)
Objective: Burning mouth syndrome (BMS) is a debilitating disorder with few limited treatment modalities. Because of the proven association between BMS symptoms, and depression and anxiety, treatment modalities that alleviate the two latter etiologic factors can be clinically effective. Thus, owing to the antidepressant and potential analgesic effects of crocin (as an active constituent of saffron), the present study was performed to compare the effect of crocin and citalopram (as control) on BMS symptoms and depression/anxiety in patients with BMS. Materials and Methods: The present double-blind randomized clinical trial was carried out on BMS patients. Patients were randomly divided into citalopram (n=21) and crocin (n=26) groups and treated for 11 weeks. BMS symptoms (based on Visual Analysis Scale (VAS)), as well as anxiety and depression (based on Hamilton questionnaire) were evaluated at baseline and during the treatment period.  Mann-Whitney, Chi-Square test, Independent t-test, Friedman, and Spearman correlation were employed for statistical analysis. Results: Our findings showed a significant effect for crocin on the severity of BMS symptoms, anxiety and depression in BMS patients. Conclusion: Crocin can be considered for treatment of BMS subjects with concurrent anxiety and/or depression.